Antimicrobial susceptibility of common pathogens isolated from postoperative intra-abdominal infections in Japan. Issue 5 (May 2018) - Takesue, Yoshio; Kusachi, Shinya; Mikamo, Hiroshige; Sato, Junko; Watanabe, Akira; Kiyota, Hiroshi; Iwata, Satoshi; Kaku, Mitsuo; Hanaki, Hideaki; Sumiyama, Yoshinobu; Kitagawa, Yuko; Nakajima, Kazuhiko; et al.
Abstract: The principle of empirical therapy for patients with intra-abdominal infections (IAI) should include antibiotics with activity against Enterobacteriaceae and Bacteroides fragilis group species. Coverage of Pseudomonas aeruginosa, Enterobacter cloacae, and Enterococcus faecalis is also recommended for hospital-associated IAI. A nationwide survey was conducted to investigate the antimicrobial susceptibility of pathogens isolated from postoperative IAI. All 504 isolates were collected at 26 institutions and referred to a central laboratory for susceptibility testing. Lower susceptibility rates to ciprofloxacin and cefepime were demonstrated in Escherichia coli . Among E. coli, 24.1% of strains produced extended-spectrum β-lactamase (ESBL). Carbapenems, piperacillin/tazobactam, cephamycins/oxacephem, aminoglycosides, and tigecycline had high activity against E. coli, including ESBL-producing isolates. Among E. cloacae, low susceptibility rates to ceftazidime were demonstrated, whereas cefepime retained its activity. P. aeruginosa revealed high susceptibility rates to all antimicrobials tested except for imipenem. Among B. fragilis group species, low levels of susceptibility were observed for cefoxitin, moxifloxacin, and clindamycin, and high susceptibility rates were observed for piperacillin/tazobactam, meropenem, and metronidazole. Ampicillin, piperacillin, and glycopeptides had good activity against E. faecalis . Imipenem had the highest activity against E. faecalis among carbapenems. In conclusion, we suggested the empirical use of antimicrobials with the specific intent of covering the main organisms isolated from postoperative IAI. Piperacillin/tazobactam, meropenem, or doripenem, are appropriate in critically ill patients. Combination therapy of cefepime (aztreonam in patients with β-lactam allergy) plus metronidazole plus glycopeptides, imipenem/cilastatin or cephamycins/oxacephem plus ciprofloxacin plus metronidazole are potential therapeutic options.